Venture capital investment : an agency analysis of practice - Reid, Gavin C. (Routledge, 1998)
This book consists of a series of in depth case studies of investor-investee relations, based on extensive empirical research and organized around the principal-agent method, which provide valuable insights into modern UK venture capital practice.